Note su lotte di classe, nazione e internazionalismo in Engels e Marx. A partire da un libro di Domenico Losurdo - Cacciatore, Fortunato M. (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2021)
The aim of this article is to reflect on the complexity of the relationship between class struggles and the “national question”; To this end, the texts of Marx and Engels are compared with those of some of their contemporary counterparts. This partial reconstruction of a much broader and articulated debate is rooted in Domenico Losurdo’s work on the concept of “class struggles”. Class struggle; National question.